A New Control Strategy for Single-Phase PWM Boost-Type Inverters - Komurcugil, Hasan (IEEE, 2011)
This paper proposes a control strategy for single-phase PWM boost-type inverters. The idea in this strategy is to have feedforward and feedback terms in the control variable. It is shown that the output voltage follows its reference without any error when there is a perfect match between estimated and actual filter capacitance. However, there exists a steady-state error in the output voltage due to the mismatch between estimated and actual filter capacitance. It is shown that this error can be minimized considerably if the controller gain is chosen as large as possible. The feasibility and the performance of the proposed control strategy has been tested and verified by simulations and experiments under linear and nonlinear loads.
ICELIE/IES Industry Forum/37th Annual Conference of the IEEE Industrial-Electronics-Society (IECON) -- NOV 07-10, 2011 -- Melbourne, AUSTRALIA
Keywords: Voltage-Source; Drive System